Komunicirati o grafičnem romanu - niz delavnic - Krameritsch, Hans (Revija za elementarno izobraževanje, 2017)
The graphic novel as a development of the last decades and now an independent art form is the focus of this text. A graphic novel workshop series is presented as an example. This took place within the framework of a teacher-training course in the Saharan refugee camps in Algeria. With the possibilities of the graphic novels, contents from the professional field of the participants were developed by means of art education and design, in the sense of reflecting their own work events, the work reference, for themselves and for others. Self-created stories from day-to-day business were developed in detail in the form of successive pictures and picture elements, partly by incorporating writing.
Keywords: grafični roman; stripi; begunska taborišča; Alžirija; delavnice; izobraževanje učiteljev